Sportmedizin im Wandel - De Souza Silveira R; Kratzenstein S; Hain G; Mayer F; Carlsohn A; 2 (Deutsche Zeitschrift für Sportmedizin)
Adolescent athletes are a vulnerable target group for nutritional education and nutritional interventions. Although the level of nutritional knowledge and food literacy should be known before conducting nutritional interventions, there is no valid tool available to assess the nutritional knowledge of German adolescent athletes. Thus, the aim of the study was to modify and validate an internationally established nutrition knowledge questionnaire for adults for use in German adolescent athletes. The General Nutrition Knowledge Questionnaire (GNKQ) was translated into German and subsequently tested in two phases. In total, 75 adolescent athletes (40 m/35 f; 14 1 years) attending Elite Schools of Sports participated. First, 34 participants answered 45 questions allocated into four knowledge sections. All questions correctly answered by 80% or 20%, were eliminated as part of the validation strategy (N=13 questions). The remaining questions were then analyzed for internal and test-retest reliability, with 41 new participants completing the validated version. Overall, reliability values of the validated questionnaire were 0.86 (Cronbachs alpha) and 0.92 (Pearsons correlation coefficient). Taken together, participants answered 48 21% of the questions correctly (males: 50 11% vs. females: 45 9%, p = 0.03). In conclusion, with this modified GNKQ it is now possible to reliably assess the nutritional knowledge and food literacy of German adolescent athletes and to use this modified assessment tool to measure improvements evoked by nutritional education programs.KEY WORDS: Nutritional Knowledge, Adolescent Athletes, Questionnaire, Validity and Reliability